The Oxford Handbook of Personnel Assessment and Selection 2012
DOI: 10.1093/oxfordhb/9780199732579.013.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Validity and the Process of Validation

Abstract: In this chapter we first set the stage by focusing on the concept of validity, documenting key changes over time in how the term is used and examining the specific ways in which the concept is instantiated in the domain of personnel selection. We then move from conceptual to operational and discuss issues in the use of various strategies to establish what we term the predictive inference, namely, that scores on the predictor measure of interest can be used to draw inferences about an individual's future job be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The most recent versions of both these documents treat validity as a unitary concept that is supported by a variety of evidence. However, thinking about validity continues to develop, as evidenced in two excellent reviews of the literature (see Kehoe & Murphy 2010, Sackett et al 2012 Van Iddekinge & Ployhart (2008) summarized the implications of several new developments to the estimation of criterion-related validity. They pointed out that underestimates of validity are likely if one does not correct for artifacts, but the correct formulas and estimates of the unrestricted range are often difficult to ascertain.…”
Section: Evidence Of Test Validitymentioning
confidence: 99%
“…The most recent versions of both these documents treat validity as a unitary concept that is supported by a variety of evidence. However, thinking about validity continues to develop, as evidenced in two excellent reviews of the literature (see Kehoe & Murphy 2010, Sackett et al 2012 Van Iddekinge & Ployhart (2008) summarized the implications of several new developments to the estimation of criterion-related validity. They pointed out that underestimates of validity are likely if one does not correct for artifacts, but the correct formulas and estimates of the unrestricted range are often difficult to ascertain.…”
Section: Evidence Of Test Validitymentioning
confidence: 99%
“…Modern conceptualizations of validation use the term to refer to the process of gathering evidence to support the inferences one wishes to draw from a score (Sackett et al., 2012). Thus, validity is not a property of an assessment per se, but of these inferences.…”
Section: Factors On Which Selection Procedures Are Evaluatedmentioning
confidence: 99%
“…In the selection context, this predictive inference is most central, and different validation strategies can be used to establish this inference (Sackett et al., 2012). Two broad categories of strategies reflect the classic distinction drawn by Wernimont and Campbell (1968) between “signs” and “samples.” A “sign” strategy views scores on a predictor as a sign or signal of future performance and relies on evidence that individuals with higher predictor scores subsequently perform better on a criterion on interest (labeled “criterion‐related validity”).…”
Section: Factors On Which Selection Procedures Are Evaluatedmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the problem with estimating the diversity-validity tradeoff, we need to understand how selection, performance, and diversity work together. To organize this discussion, a multilevel theoretical model depicting the relationships of interest, inspired by Sackett et al (2012), can be found in Figure 1. At its base, the point of employee selection is to find individuals who are good fits for open positions.…”
Section: Underestimation Of Diversity Benefitsmentioning
confidence: 99%